The Influence of Various Light Intensity and Natural Feeds To The Growth of Abalone Haliotis squamata In Aquaculture System - Latuihamallo, Magdalena (Aquacultura Indonesiana, 2014)
Aquaculture technology of abalone is commonly using traditional method in which natural resources are used as the primary inputs. Recent studies however showed that light intensity could also enhance the apetite of abalone despite of food types and concentrations. This study was emphasized at investigating light intensity individually or sinergistically with food types and concentrations in enhance growth rates of abalone. A randomised complete factorial design with three different treatments of light intensities (0 luxes, 250 luxes, and 500 Luxes), two levels of food resources (Gracillaria licheinodes and Ulva fasciata), and three levels of food percentage (20%, 22.5% and 25%) for three replicates were held. The result showed that light intensity, food types and food concentration significantly affected the growth rates of abalone. Light intensity of 250 luxes with food type of Ulva fasciata at the level concentration of  22.5% resulted on the highest growth rate, both at laboratory level and in the field (sea). The highest growth rate of abalone was found in the outdoor system, maximum ages of 8.5 years, maximum length of 114 mm, and maximum weight of 44 g.